Estrutura e ultraestrutura do epitélio epididimário de búfalos (Bubalus bubalis) em diferentes idades - SANTOS, Jeannie Nascimento dos (Universidade Estadual de Campinas, 2018)
The zonation of the buffalo epididymis of Mediterranea (Me), Murrah (mu) breeds and croosbreed Me x Mu was studied in 4 to 36 month old animals. These buffalos were c1assified in two groups, the animals which have not reached puberty (sexually immature) and animals (mature animals) and their epididymis was divided in 7 subregions called A to G. each subregion was analysed with and transmission electron microscopy. Light microscopy inc1uded routine staining with Hematoxilin & Eosin (HE), histochemistry with P AS and morphometric analysis for tubular and luminal diameters and height of epithelium and stereocilia. Throughout the epididymary tubule it was observed with light microscopy that tubules of alI ages have Principal cell (P), basal cell (B), Apical ceeII (A) and intraepithelialleukocytes (LI). Mitotic figures in the apical region of the epithelium are also found and are more numerous in the B and C subregions, specially in buffalos between 5 and 9 months of age. Histochemical analysis revealed the existence of secretory activity from the 5th month of age, principally in the A subregion, where the activity increases with sexual maturation. Morphometric analysis supports the idea that the buffalos which have not reached puberty already havee weell determined diameters and height variations of the tubule, lumen, epithelium and stereocilia. These variations were similar to that observed in buffalos after puberty. Tubular and luminal diameters increase from the A to G subregions while the height of epithelium and stereocilia diminish. However, in both morphometric features a significant difference (p<O.O5) was verified between the subregions of the animals sexually immature and animals after puberty. Ultraestructural features of the epididymary epithelium in both age ranges reveal no differences among the A and P cells; B cells appear to be reserve cells, while LI are similar to lymphocytes and macrophages. In P cells Llltrastructural features suggestive of secretory and absorptive activities were found in varying intensities in alI subregion, specially in buffalos after puberty. The 4 month old mimal already had an accentuated epithelial activity in its caudal subregions (P and G). The G subregion had large cytoplasmic and intranuc1ear paracristalline structures, similar to that Jbserved in E, P and G subregions of buffalos after puberty. These structures are probably !lssociated protein storage.